One‐step Modification of Active Sites and Support in Ni/Al2O3 Catalyst for Hydrodeoxygenation of Lignin‐derived Diphenyl Ether. Issue 41 (2nd November 2018) - Yang, Kaixuan; Chen, Xiao; Lafaye, Gwendoline; Especel, Catherine; Epron, Florence; Liang, Changhai
Abstract: A bifunctional Ni2 Si/SiO2 ‐Al2 O3 catalyst was prepared by one‐step chemical vapor deposition (CVD), and used for hydrode‐oxygenation (HDO) of diphenyl ether (DPE). During the one‐step CVD process, metallic Ni species as the HDO active sites were isolated by intermetallic modification of Si atoms and partial electron transferred from Ni to Si, as inferred by XRD, XPS, and theoretical calculation. Furthermore, the characterization results revealed that the acidity and structure of Al2 O3 were tuned due to the formation of Al‐O−Si bonds. Consequently, compared with Ni/Al2 O3 catalyst, the Ni2 Si/SiO2 ‐Al2 O3 catalyst showed a higher benzene selectivity (60% vs 47%), O‐free products selectivity at the similar conversion of DPE, and high stability for the HDO of DPE. This work provides insight for design of bifunctional catalysts with specific catalytic properties by one‐step CVD method. Abstract : A novel bifunctional Ni2 Si/SiO2 ‐Al2 O3 catalyst was prepared from Ni−Al‐LDHs by one‐step CVD. During the CVD process, not only Ni2 Si metal silicide was prepared, but the structure of support was modified. Consequently, compared with Ni/Al2 O3 catalyst, the Ni2 Si/SiO2 ‐Al2 O3 catalyst showed a higher benzene selectivity, deoxygenation activity, and stability for the hydrodeoxygenation of diphenyl ether.